Torture Is Not Protected Speech: Free Speech Analysis of Bans on Gay Conversion Therapy - Mason D. Bracken (Washington University Journal of Law & Policy, 2020)
As state and municipal bans on conversion therapy sweep the nation, questions are mounting over whether sexual orientation change efforts (SOCE) are protected speech under the First Amendment. The Supreme Court in National Institute of Family and Life Advocates v. Becerra in 2018 injected tremendous uncertainty into this area when it abrogated the reasoning of both Circuit Court of Appeals decisions that had upheld the validity of state SOCE bans against free speech challenges. Most courts and scholars in this area fall into the trap of the speech-and-action distinction, failing to ask the important threshold question: is this kind of communication covered by the First Amendment? This paper argues for a paradigm shift: conversion therapy is not covered by the Free Speech Clause, and thus, legislation banning it is valid. Analysis of this issue reinforces the argument that courts and scholars should take more seriously the distinctions between free speech coverage and free speech protection.
Keywords: gay; gay conversion therapy; conversion therapy; free speech; National Institute of Family and Life Advocates v. Becerra; First Amendment